Levels of Social Media Engagement and Academic Performance among Intermediate Grade Learners of Jolo Elementary School - Palma, Elsa T.; Tabangay, Jennifer; Jerunggay, Michelle S. (International Journal of Education and Teaching Zone, 2024)
The relationship between social media engagement and academic performance remains contentious in educational discourse. This study employed a descriptive-correlational research design, utilizing an adapted questionnaire to examine social media engagement patterns and their impact on academic performance among elementary learners. The research encompassed a total enumeration approach involving 77 pupils from grades IV to VI at Jolo Elementary School in Palawan, Philippines. Data were analyzed using descriptive statistics, encompassing frequency counts, percentages, and means. The findings revealed that 51.94% of the participants operated at an instructional reading level, 28.57% at an independent level, and 19.48% at a frustration level regarding academic performance. Furthermore, a moderate level of behavioral, affective, and cognitive engagement was identified in the pupils’ social media usage. These insights underscore the need to develop targeted interventions to address and manage excessive social media consumption among elementary pupils within educational environments